Komunikasi Keselamatan dan Work Engagement sebagai Penentu Perilaku Keselamatan Kerja pada Industri Pelabuhan - Herdian Tobo; Nahria Nahria; Muhammad Nur Jaya (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2026)
Occupational safety is a critical issue in high-risk work environments, such as container terminal operations. This study aims to analyze the effect of effective communication on employees’ safety behavior, with work engagement as a mediating variable at PT Pelindo–Peti Kemas Jayapura. The research employed a quantitative approach with an explanatory research design. The population comprised all employees of PT Pelindo–Peti Kemas Jayapura, using a saturated sampling technique with 94 respondents. Data were collected through Likert-scale questionnaires and analyzed using path analysis with SPSS. The results indicate that effective communication has a positive and significant effect on employees’ work engagement. Furthermore, both effective communication and work engagement have a direct positive and significant impact on safety behavior. The findings also confirm that work engagement mediates the relationship between effective communication and safety behavior. This study highlights that clear, open, and participative communication not only enhances employees’ psychological engagement but also fosters consistent safety behavior in daily operations. Practically, these findings provide important implications for management in strengthening safety culture through effective safety communication systems and enhancing employees’ work engagement in high-risk industrial settings.